DYNAMICS OF ATP-POSITIVE DENDRITIC CELLS IN RAT’S OROPHARYNGEAL SUBMUCOSA AFTER ANTENATAL ANTIGEN ADMINISTRATION - Hryhorieva, O.A.; Matvieishyna, T.M.; Topolenko, T.A. (World of Medicine and Biology, 2020)
Purpose of the work was to establish dynamics and morphology of DCs, located in oropharyngeal submucosa the postnatal period after antenatal antigen effect on a fetus. DCs were detected on the cryostat sections of the pharynx tissue by using the Vakhshtein-Meizel method. In experimental newborns, the DCs absolute number was found to be greater than in the control and did not change during the first week, unlike in the control, where this index did not change significantly over the two weeks of life. All groups of animals have been increased DCs absolute number by third week of life, while the antigen load on the body increases. Experimental animals, regardless of the antigen administration mode, have been taken place DCs activation earlier than in control, that is, at 7th life day. Animals which underwent antenatal antigen administration during fetal period has been increased number of their processes compared to control. Although it was founded that DCs in experimental groups are stained more shade than in control group, which indicating a more active ATP accumulation.
Keywords: ATP; antenatal antigen administration; dendritic cell; pharynx; local immunity